Tinjauan Etika Bisnis Islam terhadap Praktik Jual Beli Sistem Preloved pada Shopee - Nisrina Jameela; Eva Misfah Bayuni; Nanik Eprianti (UNISBA Press, 2024)
Abstract. Buying and selling is a form of social interaction that is often carried out by all humans. Doing business must adhere to the basic principles of Islamic business ethics. Business and ethics should not be seen as two opposing things in Islamic economics, in fact buying and selling using online systems tends to ignore ethics. Even though there are many free trade ideas emerging, debates and competition which ultimately give rise to enthusiasm among business people to justify various ways of selling their products in online shops. Prelovedboo online shop buying and selling practices on Shopee describe the product as having